Study of Patterns of Dermatoses in Pediatric OPD at Provincial Hospital of Nepal - Devkota, Askal; Bista, Muna; Paudel, Krishna Prasad (Nepal Journal of Health Sciences, 2024)
Introduction: Dermatoses are common among children and are one of the most frequently encountered conditions in pediatric OPD. Child differ from adult in presentation and management of dermatological problems. The pattern of disease is influenced by hygiene, nutritional status, overcrowding, climate and geography.Objective: Objective of the present study was to find out the pattern and prevalence of various dermatological conditions presenting in pediatric OPD of a district hospital in central Nepal.Methods: A prospective observational study was done in pediatric OPD of Sindhuli district hospital from patients of first day of life to 16 years age group from February 2021 to October 2021. Sample size of the study was 268. After physical examination a provisional diagnosis was made and patient was consulted with dermatologist to confirm the diagnosis. The findings were recorded and data was analyzed.Results:  Majority of patients (100, 37.5%) belonged to the preschool age group of 1-5 years. The ratio of male to female was 1.29:1. Majority of dermatoses belonged to infectious group (137, 51%). Among infections fungal infections was most common (54, 39.5%) followed by bacterial infections (34, 24.8%).Conclusion: This study showed the pattern of pediatric dermatoses in pediatric OPD of Sindhuli district hospital with high frequency of infectious dermatoses and preschool age group was most affected. This increase incidence of infectious dermatoses can be reduced by improving sanitation, hygiene and nutrition of children. There is also a strong need for strengthening community dermatology as recommended by WHO.